1998
DOI: 10.1126/science.279.5348.234
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the Cardiac Calcium Release Channel (Ryanodine Receptor) by Poly-S-Nitrosylation

Abstract: Several ion channels are reportedly redox responsive, but the molecular basis for the changes in activity is not known. The mechanism of nitric oxide action on the cardiac calcium release channel (ryanodine receptor) (CRC) in canines was explored. This tetrameric channel contains approximately 84 free thiols and is S-nitrosylated in vivo. S-Nitrosylation of up to 12 sites (3 per CRC subunit) led to progressive channel activation that was reversed by denitrosylation. In contrast, oxidation of 20 to 24 thiols pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
688
2
10

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 928 publications
(720 citation statements)
references
References 44 publications
20
688
2
10
Order By: Relevance
“…Furthermore, DNA microarray analysis showed that CHOP is induced by IL-1b plus IFN-g in primary rat b-cells. 85 In type II diabetes, impaired insulin action, which is often associated with obesity and physical inactivity, is a major factor in progression of the disease, but hyperglycemia occurs only when b-cells fail to compensate for the increased demand for insulin secretion. Overload of b-cells in conditions such as hyperglycemia, obesity and long-term treatment with sulfonylureas leads to b-cell dysfunction and to apoptosis through a process referred as 'b-cell exhaustion'.…”
Section: Diabetesmentioning
confidence: 99%
“…Furthermore, DNA microarray analysis showed that CHOP is induced by IL-1b plus IFN-g in primary rat b-cells. 85 In type II diabetes, impaired insulin action, which is often associated with obesity and physical inactivity, is a major factor in progression of the disease, but hyperglycemia occurs only when b-cells fail to compensate for the increased demand for insulin secretion. Overload of b-cells in conditions such as hyperglycemia, obesity and long-term treatment with sulfonylureas leads to b-cell dysfunction and to apoptosis through a process referred as 'b-cell exhaustion'.…”
Section: Diabetesmentioning
confidence: 99%
“…Concomitantly, NO derived from NOS 1 in the SR nitrosylates RyR channel proteins in a manner that promotes Ca efflux from the SR, causing contraction [19]. NO signaling by nitrosylation is fast, reversible, and affected by the overall nitroso-redox balance of the system [20]. The oxidase enzymes NADPH oxidase and xanthine oxidase, as well as mitochondrial oxidative phosphorylation, generate the biologically relevant reactive oxygen species superoxide, hydrogen peroxide and the hydroxyl radical [21].…”
Section: Nitric Oxidementioning
confidence: 99%
“…For example, NO oxidizes vicinal thiol groups to form disulfide (51). This oxidation reaction appears to occur via formation of an intermediate nitrosothiol to increase or decrease the activity of proteins such as p21 RAS (52), the olfactory cyclic nucleotide-gated channel (53), glyceraldehyde-3-phosphate dehydrogenase (54), caspase-3 (55), and ryanodine receptor (56).…”
Section: No and Signal-transduction Pathwaymentioning
confidence: 99%